Exploring Xenophobia in South Africa through Sociocultural Len - Soe, Aung Mya (NIDA Development Journal, 2023)
This paper addresses the problem of Xenophobia in South Africa. The purpose of this paper is to find out the factors that caused Xenophobia, the challenges and solutions for rebuilding social cohesion and reducing inequality in South Africa. The research is based upon theoretical concept of Galtung’s violence and conflict triangle, and the scapegoating hypothesis of Duncan. Library research method was used and literature, reports and documents were analyzed. The preliminary findings are the social problems such as unemployment, lack of housing and prejudice over business rival immigrants, and the cultural factors comprising language, clothing, music and traditions of black immigrants; the driving factors causing Xenophobia. This paper concludes that public sector commitment to engage in skill development for employment, administering provision of affordable housing and promoting cultural diversity with structural transformation, can help heal the Xenophobia, alleviate discrimination and promote equality in the divided South Africa.